Variation of Gelatin Amount as Template for Mesoporous Silica-Alumina Synthesis based on Lapindo Mud - Nuryanto, R.; Trisunaryanti, W.; Triyono (Asian Journal of Chemistry, 2020)
The synthesis of mesoporous silica-alumina from Na2SiO3 and NaAlO2 solutions extracted from lapindo mud using mesoporous gelatin templates from catfish bone extract has been performed. Mesoporous silica-alumina (MSA) synthesis was carried out by sol-gel method with a gelatin template of catfish bone for as much as 0.0; 0.5; 1.0 and 1.5 g, which produced MSA-G00, MSA-G05, MSA-G10 and MSA-G15, respectively. The obtained MSA was analyzed using FTIR, XRD, TEM and surface area analyzer (BET and BJH methods). The MSA-G00, MSA-G05, MSA-G10 and MSA-G15 showed a specific surface areas of 24.58, 41.73, 59.73, 89.82 m2/g and pore diameters of 10.20, 3.86, 9.97, and 7.31 nm, respectively. The XRD results proved that all the MSA were amorphous while the TEM analysis showed that all prepared MSAs using gelatin as a template were wormhole-like pores.